PERAN STRATEGI PENGEMBANGAN BISNIS DAN KELEMBANGAAN EKONOMI TERHADAP KEBERHASILAN PENGEMBANGAN AGRIBISNIS UBI JALAR (Ipomoea batatas L): (Suatu Kasus Pada Petani Ubi Jalar di Kecamatan Pamulihan, Kabupaten Sumedang, Provinsi Jawa barat ) - Ardiyanto (OrchidAgri, 2025)
ARDIYANTO, 2024. The Role of Business Development Strategy and Economic Development on the Success of Sweet Potato Agribusiness Development (Ipomoea batata, L). (A Case of a Sweet Potato Farmer in Pamulihan District, Sumedang Regency, West Java Province). Under GuidanceUnder the Guidance of Euis Dasipah and Dety Sukmawati This study aims to determine the Effect of Sweet Potato Business Development Strategy and the Role of Economic Institutions on the Success of Sweet Potato Agribusiness Development. The unit of analysis is sweet potato farmers in Pamulihan District, Sumedang Regency. D8imbil respondents with simple random method sampling obtained 70 units. Analysis techniques are used path analysis (path analyze). The results of the study were obtained by the Sweet Potato Business Development Strategy Demonstration a set of objectives, policies, plans, and activities of companies or business actors consisting of dimensions:P product development; Market Development, Capital Development, Cooperation/Collaboration; and Sustainability obtained 77.82% Good criteria. Economic Institutional Demonstration related to Sweet Potato Business Development includes the following dimensions: Marketing Institution; Institutional Production Input Providers; Financial Institutions; Institutional Research and Technology; Institutional Processing; and the Institutional Farmer Group obtained an achievement rate of 77.41% Good criteria. Successful Development of Sweet potato agribusiness is an effort to adapt to market changes, expand business reach, and increase the business value of sweet potatoes. Consists of dimensions: Market Adaptation; Business Expansion; and Increased Business Value obtained an achievement level of 73.89% Good criteria. There is a positive relationship between the Business Development Strategy and the Sweet Potato Agribusiness Development Economic Institution which is shown by a correlation coefficient of 0.88. Sweet potato business development strategy and economic institutions have a positive effect on the success of sweet potato agribusiness development. The respective contributions are 45.65% and 33.30% indicating the contribution of the Sweet Potato Business Development Strategy is greater. Keyword: Strategy. Development. Institutional, Success, Sweet Potato